RELATIONSHIP OF EDUCATION AND HEALTH - Ibragimova , Laylo; Hodiyeva , Marjona (Innovative Development in Educational Activities, 2024)
Studies consistently show that people with more education tend to have better health. This is because education equips individuals with the knowledge and skills to make informed decisions about their health and to access healthcare services. Additionally, higher education is often linked to higher income, which can provide greater access to healthcare and healthier lifestyle choices. However, it is important to acknowledge the bidirectional nature of this relationship, as poor health can also impact educational attainment. Policymakers and educators must recognize and address the interconnectedness of education and health in order to promote overall well-being and improve the lives of individuals and communities.